PEMBERDAYAAN KADER POSYANDU DALAM MENJAWAB TANTANGAN ZERO STUNTING - Maulana Iskandar; Anna Baroroh (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2022)
Stunting is a condition where a child's height is shorter than the height of a child of the same age as him. Stunting cases in Wonogiri Regency is still quite high, and this is homework for all elements of society, both the Regency Government, District Government, Village Government, Community Health Centers, and to Posyandu Cadres to reduce and eradicate stunting in the Wonogiri Regency area, especially Bulusulur Village. This Posyandu Cadre Empowerment Activity in Responding to the Zero Stunting Challenge aims to increase the active role of cadres as the spearhead who is directly in contact with the object of stunting cases, both for prevention and treatment. The method used is the PAR approach (Participatory Action Research) which begins with a planning survey to an evaluation followed by 6 Posyandu cadres in Klemut Hamlet. The material presented was Decreasing Stunting Rates through Socialization of the importance of 1000HPK and Provision of Supplementary Food from local products. The results obtained are that the participants better understand the importance of 1000 HPK in reducing and preventing stunting and increasing the creativity of the participants in making PMT products. However, the creativity of the participants can be maximized if there are training on making various PMTs both by the Puskesmas and from the Bulusulur Village Government.